Colombian English Teachers’ Professional Development: The Case of Master Programs (2018)
Master degree programs have rapidly increased in Colombia to the point where they are one of the most favored options for English teachers seeking to bolster their professional development. This survey study characterizes eighty participants, their five master programs, and their perceptions concerning the influence these graduate courses exerted on their teaching. While participants’ pedagogical and research work seemed to have benefited the most from their studies, their practices involving language policy and administration were regarded as distant from what they learnt. Findings suggest that innovation, reflection, and collaboration permeated participants’ overarching categories of development. Challenges to respondents’ integration of their newly acquired education with their teaching included competing ideologies and agendas exhibited by stakeholders in school communities.